Enzalutamide, an androgen receptor signaling inhibitor, induces tumor regression in a mouse model of castration‐resistant prostate cancer. Issue 12 (13th June 2013) - Guerrero, Javier; Alfaro, Iván E.; Gómez, Francisco; Protter, Andrew A.; Bernales, Sebastián
Abstract BACKGROUND Enzalutamide (formerly MDV3100 and available commercially as Xtandi®), a novel androgen receptor (AR) signaling inhibitor, blocks the growth of castration‐resistant prostate cancer (CRPC) in cellular model systems and was shown in a clinical study to increase survival in patients with metastatic CRPC. Enzalutamide inhibits multiple steps of AR signaling: binding of androgens to AR, AR nuclear translocation, and association of AR with DNA. Here, we investigate the effects of enzalutamide on AR signaling, AR‐dependent gene expression and cell apoptosis. METHODS The expression of AR target gene prostate‐specific antigen (PSA) was measured in LnCaP and C4‐2 cells. AR nuclear translocation was assessed in HEK‐293 cells stably transfected with AR‐yellow fluorescent protein. The in vivo effects of enzalutamide were determined in a mouse xenograft model of CRPC. Differential gene expression in LNCaP cells was measured using Affymetrix human genome microarray technology. RESULTS We found that unlike bicalutamide, enzalutamide lacked AR agonistic activity at effective doses and did not induce PSA expression or AR nuclear translocation. Additionally, it is more effective than bicalutamide at inhibiting agonist‐induced AR nuclear translocation. Enzalutamide induced the regression of tumor volume in a CRPC xenograft model and apoptosis in AR‐over‐expressing prostate cancer cells. Finally, gene expression profiling in LNCaP cells indicated that enzalutamide opposes agonist‐induced changes in genes involved in processes such as cell adhesion, angiogenesis, and apoptosis. CONCLUSIONS These results indicate that enzalutamide efficiently inhibits AR signaling, and we suggest that its lack of AR agonist activity may be important for these effects. Prostate 73: 1291–1305, 2013. © 2013 Wiley Periodicals, Inc.